(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
Celiac disease is one of an autoimmune diseasein the world and genetically linked . This disease may be cause many problems for pregnant women and their children . Tthere are many markers specific for celiac disease like anti-tissue transglutaminase and anti-gliadin antibodies which associated with development of celiac disease.In this study, we wished to determine whether there are relationship between celiac disease and fertility , effect on newborn and to identify the possible implications of these factors to disease course.Thirty female patients with a celiac disease with ages ranged between (15- 46) years were taken from (Al-Hussein Medical City/Kerbala).Control group consisted of 20 healthy people who were free from signs and symptoms of celiac disease who matched in age and gender with patients, and had no history for any celiac disease problem. TTG IgA & IgG ,AGA EASIA Kit, Generic assay ) and was studied using the enzyme-linked immunosorbent assay (ELISA) method. T-test and ANOVA and Pearson correlation used to analyze results by using SPSS version 24. P-value ≤ 0.05 was considered significant.TTG and AGA levels were increased significantly (p< 0.05) in patients compared with the control group .TTG and AGA levels were increased significantly (p< 0.05) in patients compared with the control group. Also, there were significant abnormality and complication when compared with control groups. So there was significant correlation between celiac disease and infertility and there is some effect on baby of women with celiac disease